Demersal and pelagic species of fish and squid from the Patagonian shelf - Eder, Elena Beatriz (2017)
The dataset contains 2007 records of occurrence of 39 species of fish and 2 species of squid distributed on the Patagonian continental shelf and slope. This dataset describes a new and revised version of the original data published through OBIS with individual morphometrics. Specimens are representative of pelagic, demersal, demersal-pelagic, demersal-benthic and benthic habits and they were collected by commercial fishing vessels in autumn (May–June, 2001, 51 catches), winter (July–August, 2001, 38 catches) and summer (January-February, 2002, 112 catches). The sampling was carried out with bottom trawls at a depth range of 73–370 m. The survey was located between 39°–52°S and 55°–65°W.